P856 The gut microbiota composition and metabolic activity of HLA-B27 transgenic rats with gut inflammation resembles the dysbiotic characteristics of human inflammatory bowel disease. (16th January 2018) - Svolos, V; Nichols, B; Bolognini, D; Quince, C; Ijaz, U Z; Papadopoulou, R T; Ansalone, C; Salmond, J; Klopfleisch, R; Gaya, D R; Russell, R K; Hansen, R; et al.
Abstract: Background: inflammatory bowel disease (IBD) is characterised by gut microbial dysbiosis, in terms of bacterial composition and functionality. HLA-B27 (B27) transgenic rat is an established model of gut inflammation often employed to study human IBD. The extent to which the microbiota of this model resembles this of human IBD has not been reported in the literature. This study aimed to describe comprehensively the microbiota characteristics of B27 rats compared with their healthy HLA-B7 (B7) counterparts. Methods: Faecal samples of adult B27 and B7 rats (40–47 weeks) were collected the day prior to sacrifice. Caecal contents, caecal, ileal and colonic tissue and plasma were harvested at sacrifice. Intestinal inflammation was quantified by blinded histological scores. The relative expression (ΔΔCt) of tissue TNFα gene, plasma concentration of CCL-2 and faecal water content were measured. Short-chain fatty acids in faeces and caecal content were measured with GC and microbiota composition was characterised using 16s rRNA gene sequencing. The concentration and total amount of bacteria in caecal content was measured with real-time qPCR. Results: As expected B27 rats had higher inflammatory histology scores in ileum and colon, higher relative gene expression of caecal and colonic TNF-a, plasma CCL-2 and faecal water content (ΔMean, +2.3, +4.1, +6.6, +5.2, +44.9ng/ml, +15.7%, all p < 0.05) compared with the B7 rats. The total caecal amount of butyrate, valerate, iso-butyrate and iso-valerate were significantly lower in B27 compared with B7 (ΔMean μmol, −89.5, −1.2, −0.9, −0.6, all p < 0.05). Similarly, the faecal concentration of butyrate was significantly lower, while that of acetate and propionate significantly higher (ΔMean μmol/g stool, −9.7, +64.7, +3.4) in B27 than B7 rats. The total number of bacteria in caecal content (ΔMean, −0.4 log10 16SrRNA gene copies) was lower in B27 rats and their microbial community was characterised by a lower α-diversity (Chao and Shannon) than the B7 group ( p < 0.03). The microbiota structure (β-diversity) of B27 rats in faeces ( p = 0.04) and in caecal content ( p = 0.03) was distinct of that of the B7 rats, with the group effect explaining 42% of the variation. Out of 92 genera, the relative abundance of 42 (45.7%) was significantly different between the B27 and B7 groups in faeces. This was the case for 32 of the 104 (30.8%) genera in caecal content. Conclusions: B27 transgenic rats present dysbiotic characteristics similar to human IBD, including the lower microbial diversity, the distinct microbiota structure and the reduced abundance of butyrate producing bacteria when compared with healthy status. This suggests that a monogenic cause of intestinal inflammation can drive microbial changes similar to those seen in human IBD.